The Association of Nonalcoholic Fatty Liver Disease with Subclinical Atherosclerosis: A Systematic Review - Caroline Johansyah; I Putu Oka Yudaswara Pande; Maria Johansyah (The International Journal of Medical Science and Health Research, 2025)
Introduction: Nonalcoholic Fatty Liver Disease (NAFLD) has emerged as a global public health issue, increasingly recognized for its strong association with cardiovascular disease (CVD), the leading cause of mortality in this patient population. This systematic review aims to comprehensively evaluate and synthesize the evidence linking NAFLD to a wide array of markers for subclinical atherosclerosis, the earliest detectable stage of CVD. Methods: A systematic search of PubMed, Google Scholar, Semantic Scholar, Springer, Wiley Online Library databases was conducted for observational studies investigating the association between NAFLD and subclinical atherosclerosis. The review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Included studies were assessed for methodological quality using the Newcastle-Ottawa Scale (NOS). Results: Synthesis of data from 17 selected high-quality observational studies, encompassing tens of thousands of participants, revealed a consistent and statistically significant association between NAFLD and multiple indices of subclinical atherosclerosis. Specifically, NAFLD was linked to increased carotid intima-media thickness (CIMT), a higher prevalence of carotid plaques, elevated coronary artery calcification (CAC) scores, and accelerated CAC progression. Furthermore, NAFLD was associated with significant functional vascular impairments, including endothelial dysfunction (manifested as reduced flow-mediated dilation) and increased arterial stiffness (measured by pulse wave velocity). These associations frequently persisted after adjustment for traditional metabolic risk factors. Discussion: The findings support the biological plausibility of NAFLD as an active contributor to atherogenesis, not merely a passive bystander. Shared pathophysiological mechanisms, including systemic inflammation, insulin resistance, and atherogenic dyslipidemia, likely drive this liver-vessel axis. The presence of NAFLD may serve as a clinical risk enhancer, identifying individuals with a heightened burden of subclinical vascular disease who might be missed by conventional risk scoring. Conclusion: NAFLD is a robust indicator for the presence of multi-site subclinical atherosclerosis. These findings underscore the importance of cardiovascular surveillance and aggressive risk factor management in individuals diagnosed with NAFLD to mitigate the long-term risk of cardiovascular events.